Clinicopathological comparison of eccrine poroma and porocarcinoma: Ki-67 index is not a decisive factor - Anna-Stiina Meriläinen; Harri Sihto; Jorma Isola; Virve Koljonen (PLoS ONE, 2025)
Background Eccrine poroma (EP) and porocarcinoma (EPC) arise from the intraepidermal part of the sweat gland. Clinically they resemble each other and cannot be distinguished without histopathological examination. EPC has been described as aggressive; however, the Ki-67 index is scarcely reported. The aim of this study was to compare clinicopathological factors between EP and EPC with special interest in Ki-67 index. Methods and Findings 50 EP and 22 EPC samples with clinical data from 48 EP and 21 EPC patients were collected from the Finnish Biobanks. We performed immunohistochemistry using a Ki-67 antibody on a tissue microarray and analysed the Ki-67 index with ImmunoRatio 2.5-program. We analysed 48 EP and 21 EPC samples. EPC patients were older (p = 0.019) and their tumours larger (p = 0.003) but other than these there were no statistically significant differences. Ki-67 ratios were similar (medians: EP 0.6% and EPC 0.5%). The median follow-up time in EP group was 12 (range 1.5–30.6 years) and in EPC group 7 years (range 0.75–20.3 years). The survival of EP patients was better than EPC patients but did not reach statistical significance and, in the Cox multivariate analysis only age had statistically significant effect (HR 1.061, 95% CI 1.026–1.099, p < 0.001). Ki-67 index had no statistically significant effect on survival in EPC group in the Cox univariate analysis (HR 0.746, 95% CI 0.390–1.43, p = 0.378). Conclusions EPC patients were older and their tumours larger. There was no difference in Ki-67 index between EP and EPC groups. In the Cox multivariate analysis only age had a statistically significant effect on survival. According to our findings Ki-67 index might not be a decisive factor in the prognosis of EPC. Further studies to validate our current findings are warranted.